Fatal drowning in the Western Cape, South Africa: a 7-year retrospective, epidemiological study. Issue 6 (24th November 2018) - Saunders, Colleen Jayne; Adriaanse, Robyn; Simons, Abigail; van Niekerk, Ashley
Abstract : Introduction: Drowning is a neglected public health threat in low-income and middle-income countries where the greatest drowning burden is observed. There is a paucity of drowning surveillance data from low-resource settings, particularly in Africa. Understanding local epidemiological factors will enable the development of context-specific drowning prevention initiatives and the appropriate allocation of resources. Aim: The primary aim of this study was to describe the epidemiology of fatal drowning in the Western Cape, South Africa. Method: This retrospective study describes fatal drowning incidents captured in the Western Cape vital registration system between 2010 and 2016. Data were obtained from the Forensic Pathology Services of the Western Cape Government. One-way analysis of variance was performed to detect a trend in mean drowning mortality rates between 2010 and 2016. χ 2 tests for independence were performed to detect differences in the distribution of variables between groups. Results: A total of 1391 fatal drownings occurred in the Western Cape between 2010 and 2016, with an age-adjusted drowning mortality rate of 3.2 per 100 000 population. Rates were fourfold higher in men compared with women. Children, particularly young children aged 0–4 years, and young adult men between 20 and 34 years of age were identified to be at high risk of fatal drowning. Drowning occurred predominantly in large, open bodies of water with concentrations in summer and public holidays. Conclusions: The Western Cape drowning prevention strategy should prioritise interventions to reduce drowning in children and young adult men, with a targeted focus on festive periods such as public holidays.